Praktek Manajemen Pengetahuan serta Dampaknya terhadap Kinerja Organisasi pada Perguruan Tinggi Swasta (PTS) di Kota Jambi - Jonner Simarmata (J-MAS (Jurnal Manajemen dan Sains), 2020)
Organizational performance  is an important issue for researchers and managers including managers in Higher Education Institutions (HEIs) for it can be the indicator of success. It also provides accurate information for startegic decision making.Many factors influence organizational performance. One of them is knowledge management (KM) practices. Theoretically and empirically, effective KM practices improve performance. Many researches have been conducted in regard of HEI performance. Unfortunately, in the context of private HEIs in the City of Jambi, the literature and empirical evidences are very rare. This current research aims to fill the gap. It also aims to examine its link with organizational performance. Data was collected through the distribution of questionnaire to randomly-selected lecturers and employees. Further, the data was analyzed with regression analysis by applying SPSS V.26. The result shows that knowledge dissemination and knowledge storage system partially and simultenously affect organizational performance. Interestingly, the constanta value in the regression model is negative. This implies that performance might be decreased if KM is not implemented. Then, it is suggested to private HEI operators especially those in the City of Jambi implement KM.